“No one gives you a rulebook to raise a kid”: Adoptive Motherhood in The Walking Dead Video Game Series - Stang, Sarah Marie (Loading, 2019)
This article closely examines the representation of adoptive motherhood in Telltale Games’ The Walking Dead video game series. It builds off previous research which has examined The Walking Dead: Season One as an example of a ‘dadified’ game to explore the ways adoptive motherhood is represented throughout the series. More specifically, this article focuses on the series’ protagonist, Clementine, as she develops from a daughter-figure to a mother-figure. Overall, this article argues that although TWD has been discussed primarily as a dadified game and much of the extant literature on the series has focused on Lee as a father-figure, TWD series can also be read as a ‘momified’ narrative. While there are several problematic aspects in the way Clementine is portrayed, the series is notable in that it explores adoptive maternity, centralizes the experiences of non-white characters, and reinforces the message that family is not limited to blood relations. Because of its centralization of Clementine – a young, potentially queer, adoptive mother of colour – TWD series should be considered as a maternal narrative, rather than only categorized as another dadified series.